Rheological characterization of Poloxamer 407 nimesulide gels - M.N. Freitas; M. Farah; R.E.S. Bretas; E. Ricci-Júnior; J.M. Marchetti (São Paulo State University (UNESP), 2006)
The thermal gelling property of Poloxamer 407- nimesulide gels was characterized by rheological studies. Nimesulide, a local anti-inflammatory and anesthetic drug used for the treatment of acute and chronic pain, has a short duration of action and a long-acting single-dose injection would be of clinical importance. Thus a poloxamer 407 gel applied intramuscularly could prolong the release and action of nimesulide. In this study, aqueous gels with nimesulide, containing three different concentrations of Poloxamer 407, were prepared. Viscosity measurements were performed by rheologial studies to obtain the optimal sol-gel transition temperature . Poloxamer 407 gels are pseudoplastic and viscoelastic materials, which have an elastic modulus (G'), characteristic of the solid, and a viscous modulus (G''), characteristic of the liquid material. Moreover, being pseudoplastic gels, when they are deformed by shearing, their viscosity decreases. Increase of the polymer concentration increased the viscosity of the gels, which could affect the releasing process of nimesulide. Furthermore, the presence of nimesulide led to a lowering of the sol-gel transition temperature.